If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8w + -1 = -5(w + 5) Reorder the terms: -1 + -8w = -5(w + 5) Reorder the terms: -1 + -8w = -5(5 + w) -1 + -8w = (5 * -5 + w * -5) -1 + -8w = (-25 + -5w) Solving -1 + -8w = -25 + -5w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '5w' to each side of the equation. -1 + -8w + 5w = -25 + -5w + 5w Combine like terms: -8w + 5w = -3w -1 + -3w = -25 + -5w + 5w Combine like terms: -5w + 5w = 0 -1 + -3w = -25 + 0 -1 + -3w = -25 Add '1' to each side of the equation. -1 + 1 + -3w = -25 + 1 Combine like terms: -1 + 1 = 0 0 + -3w = -25 + 1 -3w = -25 + 1 Combine like terms: -25 + 1 = -24 -3w = -24 Divide each side by '-3'. w = 8 Simplifying w = 8
| 3(z-4)=22 | | 7z+3=2z+28 | | 4(s+3)=5s | | 7z=6(z+1) | | 2(t+1)=0 | | (7x-6)(x+1)=(x-2)(6x+7) | | 3+6x=54+x | | 8(t+5)-48=0 | | (x-2)(x+5)=(x-7)(x+4) | | 2(x-2)=10(x-6) | | 2x^2+21=17x | | 5x+20=12x-34 | | 6(X+2)-5X=39-(8X-9) | | 20=5(p-4) | | 6x+3=2x-9 | | 5x+9=7(x-1) | | 3w-5x-y+3w+16x-8y= | | 5(p+2)=25 | | 3(y-1)=3 | | 10(z-4)= | | 16-(x+(3/x))^2=0 | | 6xwhat+2=36 | | 4(y-3)=0 | | 3p(p+2)=0 | | (-2x^2+10x+100)/(x+5)^2=0 | | 2/3v+12=20 | | (y+3)(2y+5)=0 | | 14+12y=-16+9y | | 9x^2-4m-4=0 | | 3p/2+9/10=7p/5 | | 39-5x=4x+24 | | (x+2)(-x+1)+(3x-3)(x+2)=0 |